A Critical Review of Soil Sampling and Data Analysis Strategies for Source Tracing of Soil in Forensic Investigations - Mohd Rosdi, Nur Ain Najihah Binti; Abd Hamid, Nadirah; Mohd Ali, Saiful Fazamil; Sino, Hukil; Lee, Loong Chuen (Critical reviews in analytical chemistry, 2024)
Soil is one type of Earth material demonstrating a wide range of physical, chemical, and biological properties. As the compositional profile of soil is a product of interaction between numerous abiotic and biotic components, it tends to be unique by its geographic origin. Hence, soil is paramount for predicting source or origin in forensic provenance and intelligence, food provenance, biosecurity, and archaeology. In the context of forensic investigation, source tracing of soil could be executed by a comparison or provenance analysis. Soil compositional fingerprints acquired using analytical methods must be carefully interpreted via suitable mathematical and statistical tools since multiple sources can contribute to the variability of soil other than its provenance. This article reviews recent trends in soil sampling and data interpretation strategies proposed for source tracing of soil evidence. Performances of soil provenance indicators are also described. Then, perspectives on possible research directions guiding forensic soil provenance are proposed. This timely critical review reveals the essential idea and gap in forensic soil provenance for stimulating the development of more efficient and effective provenance strategies.